Polish Indian Hobbyists and Cultural Appropriation - Wilczyńska, Elżbieta (Studia Anglica Posnaniensia, 2018)
This article attempts to describe the Polish-American Friends Movement (PAIFM) in the context of cultural appropriation. It first describes the history of the movement by linking it to the phenomenon of playing Indian, which started in the United States in the colonial period and then was transplanted to Europe in the late 19th century. Subsequently, it briefly presents the history of the Polish hobbyism movement in Poland, pointing out the historical, social, and psychological circumstances of its development. In the next part it defines the concept of cultural appropriation and its main types according to James Young (2010). The last part is devoted to a detailed analysis of different forms of activities of the PAIFM, especially the annual week gathering, as observed by the author during the 40th gathering of Polish Indian enthusiasts in 2016. Different types of cultural appropriation and an array of consequences resulting from such a positioning are discussed. In this paper it is argued that the negative undertones of the concept obscure the complexity of the movement as a cultural phenomenon and its multiple links with Native American cultures and their present political and cultural situation.